Effects of Intranasal dexmedetomidine and esketamine for premedication on postoperative pain after tonsillectomy and adenoidectomy in children: a randomized clinical trial - Jun-wei Qi; Chuang Li; Xin-yuan Qiu; Xin-ge Wen; Hua Yin; Qing-ling Meng; Li Li; Qian Zhang; Yue-ying Zhang (BMC Anesthesiology)
Abstract Background Postoperative acute pain is a common issue in children after surgery. Our study aimed to investigate whether preoperative use of a dexmedetomidine–esketamine combination could reduce postoperative pain in children undergoing tonsillectomy and adenoidectomy and reduce side effects, such as bradycardia, hypotension or emergence delirium. Methods In this double-blind, randomised controlled clinical trial, 180 children were randomly assigned to 3 groups. 30 min before surgery, the control group received 0.9% saline intranasally (Group C), the dexmedetomidine group received intranasal dexmedetomidine at 2.0 μg·kg−1 (Group D), and the combination group received intranasal dexmedetomidine at 1.0 μg·kg−1 and esketamine at 0.6 mg·kg−1 (Group DS). The primary outcome was the area under the curve (AUC) of the pain score within 24 h after surgery. Secondary outcomes included the incidence of emergence delirium (ED), pain scores after hospital discharge, and incidence of perioperative adverse events. Results A total of 173 children completed the study. The AUC of the pain score at rest within 24 h after surgery was 37.25 (20.25–51.75) in Group C, which was higher than those in Groups D (19.25 [12.50–39.13], P < 0.001) and DS (9.50 [9.00–16.25], P < 0.001). Compared with the control group, the DS group had a lower incidence of ED (12.3% vs. 44.8%, P = 0.001). Heart rates (HRs) in groups DS (P < 0.001) and C (P < 0.001) were higher than those in the dexmedetomidine group at all time points. No serious adverse events occurred. Conclusions Intranasal dexmedetomidine combined with esketamine for premedication was associated with reduced postoperative pain in children. It can also prevent ED and had fewer side effects.